The Architecture of the Unknown - Chery L. Lucarelli; Amy L. Murzyn; Matthew J. Ridenour; Neil B. Witikko (Impacting Education, 2024)
Beginning in the summer of 2019, the College of St. Scholastica endeavored to build a flexible, adaptable EdD program grounded in the guiding principles of CPED. This meant establishing a welcoming and safe program dedicated to cultivating justice-minded change makers. It also meant constructing a curriculum that would accommodate differing student backgrounds, be responsive to fluctuating consumer demands, and function as context-inclusive in an ever-evolving and intersecting space. While this alone was certainly a challenge, we did not anticipate that a global pandemic would present the most significant test of what we had created. To accomplish the aforementioned goals, the program architecture was dependent on the following structural considerations: a broadening of the target participant profile to include students across various social sectors; the use of design thinking as an asset in supporting innovation, creativity and flexibility; the inclusion of credit-bearing “third-place” courses intended to provide open-ended space and place for community building and reflective, intentional action; and an approach to course design that encouraged risk-taking by students with a focus on cultivating mindsets and skills around equity and social justice. None of these attributes on their own provided total protection from seismic societal, cultural or market shifts. Collectively, however, they offered a unique environment for the culturing of a particular type of doctoral experience, unique in its elasticity compared to more traditional, inflexible designs. This essay details the ways in which we attempted to create an inclusive, innovative, flexible structure, as validated (and challenged) by the COVID-19 pandemic.